Effects of Olive Leaf (Oleuropein) Supplementation on Quality of Breast Meat in Broilers - İsmail Yavaş; Hatice Basmacıoğlu Malayoğlu (Journal of Agricultural Sciences)
In this study, we investigated the effect of dietary olive leaf (oleuropein) supplementation at different levels on breast meat color and pH24 in along with TBA values of breast meats which were stored at +4 °C during the 11-day in broilers. For this purpose 320 one-day-old Ross-308 chicks randomly assigned to four groups (5 replicates per group, 16 chicks per replicates). In trial, dietary treatments consist of corn-soybean meal diet without or with 125, 250 and 500 mg kg-1 oleuropein supplementation respectively. At the end of trial, two chicks per replicate were slaughtered and meat samples were collected for lipid oxidation, color and pH24 measurement. According to the obtained findings, 250 mg kg-1 oleuropein supplementation on broiler diets significantly (P<0.05) decreased TBA values (mg MDA kg-1 meat) of breast meats compared with other groups. TBA values of breast meats significantly (P<0.05) increased during storage time. While breast meat brightness (L*) and yellowness (b*) values and pH24 were not significantly (P>0.05) affected by oleuropein supplementation at different levels, redness (a*) value significantly (P<0.05) increased compared with control group. As a result of the study, it is possible to say that oleuropein demonstrated antioxidant activity linked with supplementation level and it can be used at level of 250 mg kg-1 as phytobiotic antioxidant in broiler diets.